Chromosome-level genome assembly and annotation of Gypsophila vaccaria - Chaoqiang Zhang; Jiayin Zhang; Bin Yang; Yunchen Zhao; Liang Yin; Enjun Wang; Yaqiu Zhao; Jinglong Li (Scientific Data)
Abstract Gypsophila vaccaria Sm., a member of the Caryophyllaceae family, is known for its dry mature seeds, which are widely used in traditional Chinese medicine as “Wang Bu Liu Xing”. This study presents a high-quality, chromosome-scale genome assembly of G. vaccaria, integrating Hi-C technology with PacBio and Illumina sequencing data. The final assembled genome measures 1.09 Gb in total length, with a contig N50 of 9.73 Mb and a scaffold N50 of 73.3 Mb, and complete benchmarking universal single-copy orthologs (BUSCO) for the genome and protein modes were 95.9% and 94.9%. Notably, 99.93% of the sequences are anchored to 15 pseudo-chromosomes. A total of 21,795 protein-coding genes were predicted, and repetitive elements were found to constitute 80.43% of the assembled genome. This chromosome-level genome assembly serves as an invaluable resource for future research, including functional genomics and molecular breeding of G. vaccaria.